Media Pembelajaran Pada Pembelajaran Daring Di Masa Pandemi Covid-19 - Lailatul Fithriyah; Ika Nur Faijah; Restu Nurjanah (Program Studi PGSD Kampus UPI di Serang, 2021)
Online learning has limited space and time between teachers and students. To get around these limitations, it is necessary to have a tool to be able to eliminate the dimensions of space and time between teachers and students. These tools are called learning media. Learning Media is everything that can be used to convey messages or information in the teaching and learning process so that it can stimulate students' attention and interest in learning. Learning media is the most important part to be able to make online learning successful, especially during the COVID-19 pandemic. learning media by utilizing technology as a solution to online learning problems. based on the author's experience when implementing kampus mengajar in remote areas, it was found that there are still online learning that does not utilize learning media. This research is expected to be a reference in the selection of media when learning online. This research uses a qualitative approach with a literature study method. The findings of this study are the popular learning media used when online learning, including whatsapp, Google classroom, powerpoint, and youtube. They are often used because they are easily accessible, economical, and effective for online learning.